1981
DOI: 10.1017/s0140525x00009092
|View full text |Cite
|
Sign up to set email alerts
|

Can human irrationality be experimentally demonstrated?

Abstract: The object of this paper is to show why recent research in the psychology of deductive and probabilistic reasoning does not have "bleak implications for human rationality," as has sometimes been supposed. The presence of fallacies in reasoning is evaluated by referring to normative criteria which ultimately derive their own credentials from a systematisation of the intuitions that agree with them. These normative criteria cannot be taken, as some have suggested, to constitute a part of natural science, nor can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
333
1
9

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,103 publications
(348 citation statements)
references
References 87 publications
5
333
1
9
Order By: Relevance
“…It is therefore natural to wonder whether irrational behavior can ever be definitively identified (Cohen, 1981). The primary goal of this article was to show that some apparently questionable inferences may be rational after all, but the same normative approach can be used to identify irrational behavior.…”
Section: Identifying Irrational Behaviormentioning
confidence: 99%
“…It is therefore natural to wonder whether irrational behavior can ever be definitively identified (Cohen, 1981). The primary goal of this article was to show that some apparently questionable inferences may be rational after all, but the same normative approach can be used to identify irrational behavior.…”
Section: Identifying Irrational Behaviormentioning
confidence: 99%
“…The external validity problem, which is closely allied with Cohen’s (1981) argument noted above, is that the tasks that researchers select in order to demonstrate human irrationality are not at all representative of the tasks that arise in real-world contexts, which tend to be associated with normatively accurate reasoning. Evans (2007) argues that the interpretation problem and the external validity do not hold up to close scrutiny because they fail to offer ‘complete’ accounts of the discrepancy between normative benchmarks and actual behavior.…”
Section: Pitfalls When Drawing On Normative Theoriesmentioning
confidence: 99%
“…This point of view contrasts with results found in educational contexts where clear difficulties are shown in the teaching and learning of argumentation, as well as in the analysis of reasoning. We will not enter into discussions concerning logicism within the field of psychology at this time (for example, see Cohen, 1981). We only wish to stress that the experimental results indicated that the biases, fallacies and limitations in the form of producing, understanding or solving problems with logical structures were more common than the use of the norms.…”
Section: Abstract: Argumentative Competence; Argumentation Models Of mentioning
confidence: 99%